Exploring the impact of depression, stress, and sleep disturbances on academic success in international college students - Chaliawala, Kruti S.; Vidourek, Rebecca A.; King, Keith A. (Journal of International Students, 2025)
Depression, stress, and sleep issues significantly affect international college students' success. This study examines the link between depression and various academic, mental health, and demographic factors. Data from the American College Health Association's 2022 National College Health Assessment of 13,242 international students were analyzed. 92.7% of students with moderate to high stress reported depression (χ² = 677.038, p < 0.001), and 52.2% reported sleep issues linked to depression (χ² = 2075.076, p < 0.001). Academic stress affected 82.7%, and anxiety affected 79.8% of students (p < 0.001). Higher depression rates were found among female students (67.9% vs. 32.1% for males; p